IMPROVING OBSERVATION REPORT TEXT WRITING SKILLS THROUGH THE IMPLEMENTATION OF PROBLEM-BASED LEARNING MODEL USING POWTOON APPLICATION IN JUNIOR HIGH SCHOOL - Sinta Dinar Septiana; Rusdhianti Wuryaningrum; Akhmad Syukron (JLER (Journal of Language Education Research), 2020)
The skill of writing observation report text is one of the skills that need to be mastered by class X high school students. Based on the results of observations and interviews with Indonesian language subject teachers at Arjasa Junior High School, there is a problem in the process of writing observation report text. Students have d ifficulties in starting and developing ideas, have errors in applying linguistic rules, and difficulties in compiling a text framework for the observation report. This is indicated by the low-level of difficulty in learning to write the text of the observation report: only 7 students whose grades have reached the standard grade Standard Score, 28 students do not complete. To improve the writing skills of the observation report text, it is necessary to take action by applying the Problem Based Learning (PBL) model combined with the powtoon application media. The research design used was CAR (Classroom Action Research) which consisted of two cycles starting from planning, action, observation, reflection, re-planning, action, observation, and reflection. The method used to get data is through questionnaires, interviews, observations, tests, and documentation. The results showed that student learning outcomes increased from cycle I to cycle II, namely by 45.7% or as many as 16 students who reached the standard grade increased to 80% or as many as 28 students in cycle II. Based on the results obtained, it can be concluded that the application of the PBL model with the powtoon application media can improve students' skills in writing observation report text in class X IPA 4 Arjasa Junior High School.